1973
DOI: 10.1182/blood.v42.5.679.679
|View full text |Cite
|
Sign up to set email alerts
|

Serial In Vitro Marrow Culture in Acute Myelocytic Leukemia

Abstract: The in vitro granulocyte colony-forming ability of bone marrow from 19 patients with acute myelocytic leukemia (AML) was studied at the time of initial diagnosis and serially. Initially 18 of the 19 patients grew scant numbers of colonies, one produced large numbers of colonies. When clinical remission was attained and leukemic blasts in the marrow were reduced to <5%, colony forming ability usually returned to normal. Eight such patients who achieved clinical remission were serially studied during remissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Robinson et al (29,30) found repeatedly a poor response to treatment in patients whose cells did not form colonies. However, Bull et al ( 5 ) and Curtis et al (7) did not find any correlation between CFU-C and the frequency of remission. In the hitherto most extensive study of ANLL patients (n=108), Moore et al (25) concluded that the growth of small clusters (3-20 cells) or colonies (>40 cells) was related to a more favourable prognosis than if large clusters were formed or ifthere was no growth at all.…”
Section: Prognostic Injluence Of Age Und Conventionul Heniutological mentioning
confidence: 92%
“…Robinson et al (29,30) found repeatedly a poor response to treatment in patients whose cells did not form colonies. However, Bull et al ( 5 ) and Curtis et al (7) did not find any correlation between CFU-C and the frequency of remission. In the hitherto most extensive study of ANLL patients (n=108), Moore et al (25) concluded that the growth of small clusters (3-20 cells) or colonies (>40 cells) was related to a more favourable prognosis than if large clusters were formed or ifthere was no growth at all.…”
Section: Prognostic Injluence Of Age Und Conventionul Heniutological mentioning
confidence: 92%
“…We do not consider such mechanisms explicitly, but only assume the existence of some control system, which is governed by the total population of the neutrophil system consisting of both proliferative and nonproliferative cells. This assumption is the most novel and critical one that we make, and one for which we cannot provide any direct experimental evidence, although there is some indication that leukemic cells do act to inhibit the colony-forming capacity of normal proliferative cells (13,14,16). The principal justification for our assumptions resides in the comparison we shall make subsequently of the deductions from our model with some of the known kinetic characteristics of AML.…”
Section: Introductionmentioning
confidence: 98%
“…Using in vitro assays for cloning of human haemopoietic cells in vitro (Pike & Robinson, 1970) it has been repeatedly shown that cells from either bone marrow or blood of acute non-lymphatic leukaemia (ANLL) patients reveal defects of colony formation in soft-media cultures in vitro (Aye et all 1972;Bull et al, 1973;Brown & Carbone, 1971;Greenberg et all 1971;Granstrom & Gahrton, 1974;Iscove et al, 1971; Moore et al, 1973;Robinson et al, 1971;Vincent etal, 1977) or production of colony stimulating activity (CSA) (Golde et al, 1974;Goldman et al, 1976;Greenberg et al, 1971;Granstrom & Gahrton, 1974;Robinson & Entringer, 1974) in vitro.…”
mentioning
confidence: 99%